2021
DOI: 10.3390/biom11050626
|View full text |Cite
|
Sign up to set email alerts
|

Glycine-Conjugated Bile Acids Protect RPE Tight Junctions against Oxidative Stress and Inhibit Choroidal Endothelial Cell Angiogenesis In Vitro

Abstract: We previously demonstrated that the bile acid taurocholic acid (TCA) inhibits features of age-related macular degeneration (AMD) in vitro. The purpose of this study was to determine if the glycine-conjugated bile acids glycocholic acid (GCA), glycodeoxycholic acid (GDCA), and glycoursodeoxycholic acid (GUDCA) can protect retinal pigment epithelial (RPE) cells against oxidative damage and inhibit vascular endothelial growth factor (VEGF)-induced angiogenesis in choroidal endothelial cells (CECs). Paraquat was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In vitro, TUDCA promoted RPE cell integrity and diminished VEGF-induced choroidal endothelial cell migration and tube formation [ 242 ], as well as protecting RPE tight junctions and inhibiting choroidal neovascularization in an in vitro model of neovascular AMD [ 243 ]. Systemic administration of UDCA and TUDCA significantly suppressed rat models of laser-induced choroidal neovascularization, and the VEGF levels in the retina were lower in the treated group as compared to controls, which might be associated with anti-inflammatory action [ 244 ]. Furthermore, systemic administration of UDCA and TUDCA also preserved photoreceptors after retinal detachment and upregulated antiapoptotic, antioxidant, and anti-inflammatory genes, suggesting that their oral administration may be a potential neuroprotective adjuvant therapy in retinal detachment and other retinal degenerative diseases like AMD [ 245 , 246 ].…”
Section: Microbiota Mitochondria Intertwined Relationshipmentioning
confidence: 99%
“…In vitro, TUDCA promoted RPE cell integrity and diminished VEGF-induced choroidal endothelial cell migration and tube formation [ 242 ], as well as protecting RPE tight junctions and inhibiting choroidal neovascularization in an in vitro model of neovascular AMD [ 243 ]. Systemic administration of UDCA and TUDCA significantly suppressed rat models of laser-induced choroidal neovascularization, and the VEGF levels in the retina were lower in the treated group as compared to controls, which might be associated with anti-inflammatory action [ 244 ]. Furthermore, systemic administration of UDCA and TUDCA also preserved photoreceptors after retinal detachment and upregulated antiapoptotic, antioxidant, and anti-inflammatory genes, suggesting that their oral administration may be a potential neuroprotective adjuvant therapy in retinal detachment and other retinal degenerative diseases like AMD [ 245 , 246 ].…”
Section: Microbiota Mitochondria Intertwined Relationshipmentioning
confidence: 99%
“…CA, DCA, and UDCA are conjugated with glycine to form glycocholic acid (GCA), glycodeoxycholic acid (GDCA), and glycoursodeoxycholic acid (GUDCA), respectively, and UDCA is conjugated with taurine to form tauroursodeoxycholic acid (TUDCA). In addition to increasing hydrophilicity, conjugation of bile acids with taurine or glycine increases solubility and limits passive diffusion across the cell membrane [ 110 , 111 ].…”
Section: New Therapeutics For Amdmentioning
confidence: 99%
“…In two independent studies, Warden et al recently assessed the ability of glycine and taurine-conjugated bile acids at different concentrations, to inhibit features of AMD modeled in vitro. On the one hand they evaluated their capacity to protect human primary RPE cells tight junction integrity, assessed by ZO-1 immunofluorescence and transepithelial electrical resistance measurements, against paraquat-induced oxidative damage; and on the other hand, they tested their ability to inhibit VEGF-induced choroidal endothelial cells angiogenesis, evaluated through cell proliferation, cell migration, and tube formation assays in immortalized macaque choroidal endothelial cells [ 111 ]. With these experiments, authors found that GCA, GDCA, and GUDCA preserved RPE tight junctions’ function and structure under oxidative stress conditions.…”
Section: New Therapeutics For Amdmentioning
confidence: 99%
See 2 more Smart Citations